2019
DOI: 10.1001/jamanetworkopen.2019.4176
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Atrioventricular Block

Abstract: Key Points Question Are there readily modifiable risk factors associated with the risk of atrioventricular block? Findings In this population-based cohort study of 6146 community-dwelling individuals, elevated blood pressure and blood glucose levels were associated with the development of atrioventricular block. Population-attributable risk calculations suggest that elevated blood pressure and glucose levels may be associated with more than half of all case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 40 publications
3
38
2
5
Order By: Relevance
“…While not commonly known it has been established that conduction disorders are associated with diabetes mellitus. In a population‐based cohort study investigating 6.146 community‐dwelling individuals, increased fasting glucose levels were associated with the development of AVB 17 . In a cross‐sectional analysis of 845.747 patients at a US Veterans Health Administration hospitals, Movahed et al found diabetes to be strongly associated with third‐degree heart block 18 .…”
Section: Discussionmentioning
confidence: 99%
“…While not commonly known it has been established that conduction disorders are associated with diabetes mellitus. In a population‐based cohort study investigating 6.146 community‐dwelling individuals, increased fasting glucose levels were associated with the development of AVB 17 . In a cross‐sectional analysis of 845.747 patients at a US Veterans Health Administration hospitals, Movahed et al found diabetes to be strongly associated with third‐degree heart block 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis is also a pathophysiological hallmark of atrial fibrillation (Gal & Marrouche, ; Kottkamp, ), which has a prevalence of ~9% in those >65 years old and is a major risk factor for stroke (Piccini et al, ; Staerk, Sherer, Ko, Benjamin, & Helm, ). In the conduction system, fibrosis causes bradyarrhythmia and heart block, a substantial cause of morbidity in the elderly (Csepe, Kalyanasundaram, Hansen, Zhao, & Fedorov, ; Kerola et al, ). Risk factors for cardiac fibrosis are diverse and include hypertension (Cuspidi, Ciulla, & Zanchetti, ), ischaemic heart disease (Hinderer & Schenke‐Layland, ), aortic stenosis (Bing et al, ; Katbeh et al, ), inherited cardiomyopathy (Gulati et al, ; Ho et al, ), diabetes (Russo & Frangogiannis, ), and ageing (Lu et al, ).…”
Section: Fibrosis: a Final Common Pathway Underlying Cardiac And Renamentioning
confidence: 99%
“…(56.1%) were women, 6 where our study was carried out on evaluation of risk factors among myocardial infarction inpatients in department of coronary care unit(CCU) in territory care hospital. There is a need of providing a proper patient education regarding disease and its associated risk factors in order to minimize the recurrent chances of MI.…”
Section: Resultsmentioning
confidence: 99%